Inventory policy for the demand of main products: the case of a peruvian grocery store - Mauricio Espinoza, Joshep Delfin (2024)
The study proposed an inventory policy for its products with the highest demand based on the analysis of the application of three planning techniques, which were the Silver Meal method, the minimum unit cost method and the EOQ. In addition, forecasting techniques were applied with a bimonthly historical data from the sales record that helped identify the products with the highest demand according to the ABC classification. The methodology carried out in a grocery store in Peru found that the demand behavior differed in each product; so, the standard deviation was analyzed. Then, the application of the three planning techniques was compared where a similarity in the frequency of orders and quantity between the Silver Meal and MCU was observed; on the other hand, the EOQ functioned as a preliminary step to identify a reorder point.